Molecular and in silico typing of the lipooligosaccharide biosynthesis gene cluster in Campylobacter jejuni and Campylobacter coli. - Amber Hameed; Julian M Ketley; Alexandra Woodacre; Lee R Machado; Gemma L Marsden (PLoS ONE, 2022)
The extensive genetic variation in the lipooligosaccharide (LOS) core biosynthesis gene cluster has led to the development of a classification system; with 8 classes (I-VIII) for Campylobacter coli (C. coli) LOS region and with 23 classes (A-W) or four groups (1-4) for Campylobacter jejuni (C. jejuni) LOS region. PCR based LOS locus type identification for C. jejuni clinical isolates from a UK hospital as well as in silico LOS locus analysis for C. jejuni and C. coli genome sequences from GenBank was carried out to determine the frequencies of various LOS genotypes in C. jejuni and C. coli. Analysis of LOS gene content in 60 clinical C. jejuni isolates and 703 C. jejuni genome sequences revealed that class B (Group 1) was the most abundant LOS class in C. jejuni. The hierarchy of C. jejuni LOS group prevalence (group 1 > group 2 > group 3 > group 4) as well as the hierarchy of the frequency of C. jejuni LOS classes present within the group 1 (B > C > A > R > M > V), group 2 (H/P > O > E > W), group 3 (F > K > S) and group 4 (G > L) was identified. In silico analysis of LOS gene content in 564 C. coli genome sequences showed class III as the most abundant LOS locus type in C. coli. In silico analysis of LOS gene content also identified three novel LOS types of C. jejuni and previously unknown LOS biosynthesis genes in C. coli LOS locus types I, II, III, V and VIII. This study provides C. jejuni and C. coli LOS loci class frequencies in a smaller collection of C. jejuni clinical isolates as well as within the larger, worldwide database of C. jejuni and C. coli.